Dead Poets Society - Weir, Peter (Philippines : Viva Video, 2002)
When charismatic English professor John Keating (Oscar winner Robin Williams*) arrives at a strict boys academy, his unconventional teaching methods breathe new life into the curriculum steeped in tradition. With his wit and wisdom, Keating inspires his student to pursue individual passions and make their lives extraordinary. DEAD POETS SOCIETY, one of the most compelling box office triumphs in recent years, touched audiences and critics alike with its brilliant acting, uplifting story and superb filmmaking!